2018
DOI: 10.20944/preprints201811.0311.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Malnutrition on Long-Term Mortality in Elderly Patients with Acute Myocardial Infarction

Abstract: Background: Malnutrition is a frequent condition in the elderly and is associated with prolonged hospitalization and increased mortality. However, the impact of malnutrition among elderly patients with acute myocardial infarction has not been clarified yet. Methods and Results: We have enrolled 174 patients aged 65 years and over, admitted with the diagnosis of acute myocardial infarction (AMI) who underwent to the evaluation of nutritional status by Mini Nutritional Assessment (MNA) and of mortality risk by G… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…It is well established that malnutrition is associated with increased mortality in both acute and chronic disease, and this effect is still observed in older adults. The risk for both short-term mortality in acute conditions [ 54 ] as well as for long-term mortality in chronic disease is significantly increased [ 55 ]. One large cohort study included 1767 older individuals with a variety of disease ranging from cancer to diseases of the circulatory or respiratory system and revealed that the increased risk of mortality due to malnutrition existed irrespective of the cause of death [ 56 ].…”
Section: Impact Of Malnutrition In the Oldmentioning
confidence: 99%
“…It is well established that malnutrition is associated with increased mortality in both acute and chronic disease, and this effect is still observed in older adults. The risk for both short-term mortality in acute conditions [ 54 ] as well as for long-term mortality in chronic disease is significantly increased [ 55 ]. One large cohort study included 1767 older individuals with a variety of disease ranging from cancer to diseases of the circulatory or respiratory system and revealed that the increased risk of mortality due to malnutrition existed irrespective of the cause of death [ 56 ].…”
Section: Impact Of Malnutrition In the Oldmentioning
confidence: 99%
“…Although in univariate analysis the MPI score was significantly associated with 3-month all-cause mortality, our statistical model excluded this variable from the multivariate examination, in contrast to many scientific studies reporting that it is a robust prognostic factor in various geriatric clinical settings ( 21 - 22 ). However, the limited number of study participants might have affected the predictive efficacy of the MPI score.…”
Section: Discussionmentioning
confidence: 95%